Use of infrared thermography as internal load control in football players - Vieira, José Guilherme Bottentuit (2021)
Infrared thermography has been used to verify its capacity to determine the magnitude of the internal load of official matches to which athletes are being submitted. Objective: To analyze the behavior of the thermographic profile of the posterior muscles of the lower limbs of football athletes in the recovery period, between 24 and 48 hours, after matches. Materials and methods: According to the inclusion and exclusion criteria, the sample consisted of five athletes with a mean age of 26.0 ± 3.0 years who played four consecutive Serie A football matches in the Maranhão football championship. Thermographic images of the posterior muscles of the lower limb were performed in the post-match periods with software Apollo (Omni) and a significance level of p<0.05 was adopted.  Result and Discussion: The values ​​regarding the temperature variation, presented during the four games, showed no significant difference. Although it can be noted that from the third game, the thermography showed a gradual increase in the number of hot zone pixels compared to the first game. Thus, when an athlete performs his fourth successive official match in a short rest period between games, he may have high residual fatigue, which is one of the risk factors for injury. Conclusion: Thermography has shown that from the third game there is a gradual increase in the number of hot zone pixels compared to the first game. Thus it can be said that infrared thermography has potential in charge control, thus working to predict possible injuries